Anatomical Risk Factors for Ischemic Lesions Associated with Carotid Artery Stenting. Issue 6 (November 2014) - Ikeda, Go; Tsuruta, Wataro; Nakai, Yasunobu; Shiigai, Masanari; Marushima, Aiki; Masumoto, Tomohiko; Tsurushima, Hideo; Matsumura, Akira
The purpose of this study was to investigate the anatomical risk factors for ischemic lesions detected by diffusion-weighted imaging (DWI) associated with carotid artery stenting (CAS). DWI was performed within four days after CAS in 50 stenotic lesions between January 2008 and September 2013. We retrospectively analyzed the correlation between the anatomical factors and ischemic lesions associated with CAS. Post-procedural DWI revealed new ischemic lesions after 24 (48%) of the 50 CAS procedures. All three patients with common carotid artery tortuosity, defined as the presence of severe angulation (less than 90 degrees) in the common carotid artery, developed new ischemic lesions. However, there were no significant differences between the patients with and without tortuosity, likely due to the small number of cases. Meanwhile, seven of eight patients with internal carotid artery tortuosity, defined as the presence of severe angulation (less than 90 degrees) in the cervical segment of the internal carotid artery, developed new ischemic lesions. A multivariate analysis showed internal carotid artery tortuosity (odds ratio: 11.84, 95% confidence interval: 1.193–117.4, P= 0.035) to be an independent risk factor for the development of ischemic lesions associated with CAS. Anatomical factors, particularly severe angulation of the internal carotid artery, have an impact on the risk of CAS. The indications for CAS should be carefully evaluated in patients with these factors.